The city of entertainment as an experimentation field for improving the daily public space - Trabattoni Luca; Capotorto Margherita (Lodz University of Technology Press, 2023)
The article aims to demonstrate the value of reflection on campsite as urban laboratories. The development of the open-air tourism market has modified these settlement systems, diverting them towards integrated systems of natural and built elements. Although living on holiday represents a particular form of living, the temporality of the experience does not reduce its study value. It amplifies the market needs of citizens' desires and represents a focal case study. The accommodation facilities in the open air represent an experimental application of living in nature. The settlement system concluded in a space defined by dimensions and rules, allows a virtuous design of the open space to improve the settlement by the relationship man/nature. The aggregative space acquires a predominant value, as the basis of the anthropic landscape characterizing the accommodation itself. The reflections on the reality of outdoor tourism can be immediatly applied in a seemingly distant field: refugee camps and temporary cities. These share with the campsite the elements that make up the general structure of the settlements, renouncing the construction of the context in favour of the pragmatic nature of the intervention. The construction of the vacuum of campsite can represent an improvement revision also of emergencies.
Keywords: nature; outdoor tourism; campsite; temporary city; sustainability; przyroda; turystyka plenerowa; kemping; tymczasowe miasto; zrównoważony rozwój